Venetoclax in combination with chidamide and azacitidine for the treatment of relapsed/refractory B-cell acute lymphoblastic leukemia with the MLL-AF4 gene: a case report and literature review - Jin, Xuelian; Liu, Zhigang; Wu, Yu; Ji, Jie (Frontiers in Immunology, 2025)
B-cell acute lymphoblastic leukemia (B-ALL) with the MLL-AF4 fusion gene has a poor prognosis, and the mortality rate exceeds 90%, particularly in cases of extramedullary relapse (EMR). Herein, we present a case of a 46-year-old male patient who developed relapsed B-ALL with MLL-AF4. The patient initially achieved a complete remission (CR) after induction therapy and underwent haploidentical hematopoietic stem cell transplantation. Five months post-transplantation, he developed enlarged lymph nodes and subcutaneous masses. A lymph node biopsy confirmed EMR, without leukemia in the bone marrow or peripheral blood. The patient received the VCA regimen (venetoclax, chidamide, and azacitidine) and was regularly monitored through blood counts, marrow cell morphology analysis, flow cytometry, and computed tomography or positron emission tomography-computed tomography imaging. After the first VCA course, the patient achieved a second CR with only transient myelosuppression. Following two VCA courses, he received chimeric antigen receptor T-cell therapy, which led to complete metabolic remission and improved prognosis. This case underscores the potential of the VCA regimen as a bridging therapy for EMR in B-ALL with MLL-AF4, although further studies are warranted.